Algunas características físicas de la lluvia relacionadas con la erosión del suelo, en dos regímenes pluviométricos de Costa Rica - Jiménez, Amael; Jiménez Otárola, Francisco; Faustino, Jorge; Solís, Hernán (2016)
Rains' size, size distribution, and kinetic energy in two representative sites (Alajuela and Turrialba) of pluviometric rigemes predominant in Costa Rica (Caribbean and Pacific) were studied. Raindrops diameter ranged between 0,83 and 66 mm in Turrialba and between 0,75 and 7,1 mm in Alajuela. In both sites, raindrops' diameter was between 1 and 2 mm with a frequency of 80 percent in Turrialba and 60 percent in Alajuela. In general, kinetic energy and average diameter measured by its frequency increased as pluviometric events intensity also increased. Local adjustment of general models seems indispensable, as the one employed in the soil loss universal equation to estimate rains erosive potential.